Insect Diversity In Forest Of Mount Klabat, Kauditan Subdistrict North Minahasa Regency: Insect Diversity In Forest Of Mount Klabat, Kauditan Subdistrict North Minahasa Regency - Iwan Sixtus Umboh (Indonesian Biodiversity Journal, 2020)
This study aims to assess The population and insect diversity in the Forest of Klabat. Sequences of this study consisted of determining the location of the sample, the sample unit, and forest. This research was conducted using survey methods, identification, and analysis data. The resulting study showed that insect populations and diversity obtained from the forest of Klabat is a total of 190 individuals consisting of 29 orders and 23 families, with the amount of each individual as follows: 34 Diptera, Hymenoptera 25, 21 Coleoptera, Lepidoptera 18, .and Orthoptera 5. The population the highest of the forest that is on the order Diptera Family Lauxamidae. Insect Diversity in the forest of Klabat at altitude 301 -400 masl is H. =4,76, and in the forest of Klabat at altitude 401 – 500 masl is H. = 2,31.